Hey there!
Solving for equation: y = 9x + 2
Replace (for now) 9x + 2 for y in the equation: y = 3x + 12
y = 3x + 12
↪ 9x + 2 = 3x + 12
ADD by -3 on both of your sides
9x + 2 + (-3x) = 3x + 12 + (-3x)
If you solved that correctly you should get: 6x + 2 = 12
ADD by -2 on both of your sides
6x + 2 + (-2) = 12 + (-2)
Cancel out: 2 + (-2) because it gives you 0
Keep: 12 + (-2) because it helps us solve for our x-interpret
12 + (-2) = 10
NEW EQUATION: 6x = 10
DIVIDE by 6 on your sides
6x/6 = 10/6
Cancel out: 6x/6 because it gives you 1
Keep: 10/6 because it helps us solve for our x-intercept
10/6 = 10÷2/6÷2 = 5/3
Thus our x = 5/3
Solving for y = 9x + 2
Replace x with 5/3 since we found our x
y = 9(5/3) + 2
9(5/3) = 15
15 + 2 = 17
Thus our y = 17
Overall answer: a = 5/3 & y = 17 ✅ (Option D)
Good luck on your assignment and enjoy your day!
~LoveYourselfFirst:)